(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2019)
The study was conducted at the vegetable research field, department of horticulture and landscape design, college of agriculture and forestry, Mosul University during growing season 2017/2018, to study polyploidy chromosome in faba bean by using colchicines . The seeds of variety Sakiz were soacking in colchicines 0 ,1000 2000 and 3000 ppm for 8, 16 and 24 hours , with three replicate in RCBD Factorila experiment . The result showed that the 2000 ppm of colchicines gave the high value of number of stomata per cm2 (19.76) and in stomata length (13.07 μm). While 3000 ppm of colchicines gave the significant effect on the diameter of the stem at true leaf, number of pods/plant, total chlorophyll, plant length at first harvesting and in total seeds yield /hectar. The soacking period at 24 hours gave a significant effect on the number of stomata per cm2, stomata length, number of pods/plant, pod length, plant length at first harvesting and in total yield per unit The interaction between colchicines concentration 2000 and 3000 ppm with 24 hours gave the superior result in diameter of stem at first true leaf(5.99 cm ) , number of stomata per cm 2 (22.07) , number of pods /plant(33.00) , seed weight(2.10 gm) , seed length (2.55 cm) and in total seeds yield / hectar( 4682.55 kg/ hectar).